Hedging and Emphasis: The Use of Discourse Markers in Undergraduate Research Writing - Atiqa Iftikhar; Muhammad Khalil; Iqra Asghar (Indus Journal of Social Sciences, 2025)
This article focuses on undergraduate research writing, specifically, the use of discourse markers to hedge and emphasize. Writers use hedging devices — modal verbs, adverbs and other cautious language — to show uncertainty and avoid overgeneralisation; emphasis markers — intensifiers and assertive expressions — to strengthen key claims. This paper discusses the results of a study on the use of discourse markers in a corpus of undergraduate research papers for a limited number of authors, the frequency of the discourse markers, their types and pragmatic functions using a qualitative and quantitative methodology. Employing a mixed-methods approach, the study engages quantitative analysis to reveal usage patterns alongside qualitative discourse analysis to investigate the rhetorical effects of these terms. In the early stage of arguing, student used of emphasis markers to strengthen claims, while a poor hedging strategy adversely affected their argument, reducing its persuasion and credibility. This study highlights the significance of teaching students to use discourse markers purposefully in academic writing to help them reach rhetorical awareness and communicative effectiveness.